A HARMONY AMONG OF RELIGIOUS COMMUNITY IS REQUIRED AMIDST THE COVID-19 PANDEMIC - Tyas, E. Handayani; Naibaho, Lamhot (International Journal of Research -GRANTHAALAYAH, 2020)
This article is about a harmony among of religious community which is required amidst the COVID-19 Pandemic. It is written in to inform the religious communities especially in Indonesia to be able to live in harmonious way amidst the COVID-19 Pandemic. It is a qualitative research with the "Library Research" design, where researchers as "key instruments" by reading the theories that are directly related to the topic of "A Harmony among of Religious Community is required amidst the COVID-19 Pandemic" sourced from Pubmed, Google Scholar, Google with keywords building a culture of tolerance since early childhood. The result shows that all of Indonesian people and other nations in the world face the Covid-19 pandemic which requires togetherness and mutual assistance, the urgency of solidarity and harmony between religious believers is even more significant, because if you are careless, the Covid-19 pandemic can trigger rifts and even conflicts among the nation’s children. Educational leaders, religious leaders, community leaders, all moved to make their citizens comply with health protocols.